An Energy Balanced Efficient and Reliable Routing Protocol for Underwater Wireless Sensor Networks - Zahid Wadud; Muhammad Ismail; Abdul Baseer Qazi; Farrukh Aslam Khan; Abdelouahid Derhab; Ibrar Ahmad; Arbab Masood Ahmad (IEEE Access, 2019)
Underwater Wireless Sensor Networks (UWSNs) face numerous challenges due to small bandwidth, long propagation delay, limited energy resources and high deployment cost. Development of efficient routing strategies is, therefore, mandatory and has remained the focus of researchers over the past few years. To address these challenges and to further improve the performance of the existing protocols, many routing protocols have been designed. In Weighting Depth and Forwarding Area Division-Depth Based Routing (WDFAD-DBR), the forwarding decision is based on the weighting depth difference, which is not an efficient way for void hole avoidance. In this paper, we propose a depth-based routing mechanism called Energy Balanced Efficient and Reliable Routing (EBER2) protocol for UWSNs. First, energy balancing among neighbors and reliability are achieved by considering residual energy and the number of Potential Forwarding Nodes (PFNs) of the forwarder node, respectively. Secondly, energy efficiency is enhanced by dividing the transmission range into power levels, and the forwarders are allowed to adaptively adjust their transmission power according to the farthest node in their neighbor list. Thirdly, duplicate packets are reduced by comparing depths, residual energy and PFNs among the neighbors. Moreover, network latency is decreased by deploying two sinks at those areas of the network that have high traffic density. The results of our simulations show that EBER2 has higher Packet Delivery Ratio (PDR), lower energy tax, and lesser duplicate packets than the WDFAD-DBR routing protocol.